Combustion of a Controlled Condition Synthetic Gas with Diesel in a Single Cylinder Compression Ignition Engine - Muhammad Sani, Muhammad Husni (Universiti Teknologi Petronas, 2011)
The application of diesel engine is very wide since it is suitable for heavy-duty applications. Besides that, it is also reliable since it can last for a long period under proper maintenance. However, there are two big issues related to diesel engine nowadays, which are the depletion of liquid fuel sources and also the emission of hazardous gases from its operation. Replacing diesel fuel with another alternative like syngas is one of the many possible solutions for the problems. However, syngas from biomass gasification is known for its fluctuation of content and composition. Hence, parameters like syngas composition, combustion temperature, emission and calorific value are still questionable. In this project, imitated syngas is burned in a diesel engine and the performance and the emission of the engine is analyzed. The emitted gas from the engine is analyzed with a gas analyzer unit to observe the compositions of the exhaust gas. As for the performance, the engine unit is equipped with an instrumentation unit which will provide important parameters like engine torque and speed. The engine results in the dual fuel mode will be compared to the datum which fully diesel engine operation. At the end of the project, it is found that the engine performance is dropped as the syngas is introduced into the operation. However, it is compensated by less hazardous gases emission from the engine exhaust.